Memahami Hubungan Hukum, Pendidikan, dan Politik pada Peradaban Bani Abbasyiah - M. Ikhwan (JSI: Jurnal Sejarah Islam, 2022)
This study describes the relations of legal, education, and politic of the Abbasid civilization era which succeeded in reaching its golden age. The Bani Abbasyiah civilization deserves to be re-read in order to put the spirit and experience of civilization at that time into the present context. Civilization can’t be separated from attention to justice in law enforcement, encouragement to the development of science, as well as political will that favors the interests of the community equally. This study uses a qualitative research method with a historical approach, data sources are taken from secondary data such as books and journals, then synthesized into conclusions. The results of this study: The first, legal civilization during the Abbasid period experienced a development where law enforcement tools were formed and complete, and in making decisions always consider the opinion of the fukaha. The second, the field of education is also experiencing a very great development, all books are translated into various languages or vice versa, educational tools are adapted to the times. The third, political developments are also very good. The relationship between the three things that can be called civilization (law, education, and politics) is that political power is supported by two major forces, namely law and education, so that all three are intertwined to continue the stability of the Abbasid system.